Environment-friendly scheelite high-entropy microwave dielectric ceramic material and preparation method thereof
Through the design of high entropy components and improved solid phase reaction method, a ceramic material with excellent microwave dielectric properties at low sintering temperature was developed, which solved the problems of high sintering temperature and limited material performance in the prior art, and achieved the balance of low temperature co-fired and high performance of the material.
Patent Information
- Application Number
- CN202411882618.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing microwave dielectric ceramic materials have high sintering temperatures in low-temperature co-firing technology, which is difficult to meet the strict requirements of 5G/6G communication equipment for material performance, and the addition of sintering additives will affect material performance.
Using a high entropy component design, the ceramic material structure of Na0.5 (LaPrNdX) 0.5/NMoO4 was combined with an improved solid phase reaction method, and anhydrous ethanol was used instead of traditional polyvinyl alcohol to reduce the sintering temperature without adding sintering aids.
At a lower sintering temperature (600~740℃), ceramic materials have reasonable dielectric constant, high quality factor and near zero resonant frequency temperature coefficient, showing excellent microwave dielectric properties, and the material is placed in the air with a stable chemical composition, simple environmentally friendly and non-toxic.
Smart Images

Figure CN119661220A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic ceramics, and in particular relates to an environmentally friendly scheelite high-entropy microwave dielectric ceramic material and a preparation method thereof. Background Art
[0002] The rapid development of high-frequency communication technology has promoted the urgent demand for 5G / 6G communication equipment with larger capacity and faster transmission speed, which in turn puts forward more stringent performance requirements for microwave dielectric ceramic materials. These ceramic materials have a suitable dielectric constant (ε r ), near-zero temperature coefficient of resonant frequency (TCF) and high quality factor (Qf), play a vital role in modern communication systems and are widely used in filters, dielectric antennas, substrates and resonators. It is particularly noteworthy that the lower sintering temperature (less than 900°C) can meet the application requirements of low-temperature co-fired ceramics (LTCC) technology; the low dielectric constant can effectively reduce the delay of signal propagation, and the high quality factor ensures excellent frequency selectivity and energy efficiency. The near-zero TCF value can ensure the thermal stability of communication equipment under different temperature environments, and the ceramic material formula should be conducive to the process flow and easy to industrialize. Most traditional electronic ceramics cannot meet the material requirements of LTCC technology because the sintering temperature of the ceramics is too high. Therefore, the development of advanced microwave dielectric ceramic materials is crucial to meet the growing communication needs.
[0003] Existing microwave dielectric ceramic materials usually need to be doped with an appropriate amount of sintering aids to achieve low-temperature sintering of microwave dielectric ceramics. However, the cooling effect of doping with an appropriate amount of sintering aids on the material system is very limited, and additives often deteriorate the performance of ceramics, so it is necessary to repeatedly weigh and choose certain parameter advantages during development. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the present invention provides an environmentally friendly scheelite high entropy microwave dielectric ceramic material and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:
[0005] The embodiment of the present invention provides an environmentally friendly scheelite high entropy microwave dielectric ceramic material, the structural expression of the ceramic material is Na 0.5 (LaPrNdX) 0.5 / N MoO4, wherein X is selected from at least two of Bi, Ce, Sm, Eu, and Y, and N is the sum of the number of element species of La, Pr, Nd, and X.
[0006] In one embodiment of the present invention, the sintering temperature of the ceramic material is 600-740°C.
[0007] In one embodiment of the present invention, the relative dielectric constant of the ceramic material is 10 to 16, the quality factor is 20,000 to 50,000 GHz, and the resonant frequency temperature coefficient is -30 to -60 ppm / °C.
[0008] Another embodiment of the present invention provides a method for preparing an environmentally friendly scheelite high entropy microwave dielectric ceramic material, comprising the steps of:
[0009] S1, according to the structural expression of ceramic materials Na 0.5 (LaPrNdX) 0.5 / N MoO4 weighs Na2CO3, La2O3, Pr2O3, Nd2O3, MoO3 and rare earth oxides as raw materials, wherein X is selected from at least two of Bi, Ce, Sm, Eu, and Y, N is the sum of the element types of La, Pr, Nd, and X, and the rare earth oxides are selected from at least two of Bi2O3, CeO2, Sm2O3, Eu2O3, and Y2O3;
[0010] S2, mixing the raw materials uniformly through a primary ball milling process to obtain a primary ball milled powder;
[0011] S3, pre-sintering the primary ball-milled powder to obtain a pre-sintered ceramic powder;
[0012] S4, performing secondary ball milling on the ceramic powder to obtain secondary ball milled powder;
[0013] S5, pressing and sintering the secondary ball-milled powder to obtain the ceramic material.
[0014] In one embodiment of the present invention, step S1 includes:
[0015] La2O3, Pr2O3, Nd2O3 and rare earth oxides are placed in a muffle furnace for pretreatment. The pretreatment conditions are 700-850°C and kept warm for 3-6 hours.
[0016] In one embodiment of the present invention, step S2 comprises:
[0017] The raw materials, zirconium balls and anhydrous ethanol are placed in a ball mill according to a mass ratio of 1:2:1 for primary ball milling. The primary ball milling parameters are: speed 200-300 r / min, time 3-6 h, to obtain the primary ball milled powder.
[0018] In one embodiment of the present invention, step S3 includes:
[0019] The first ball-milled powder is dried, and the dried powder is pre-sintered at 550-650° C. for 4-8 hours to obtain the pre-sintered ceramic powder.
[0020] In one embodiment of the present invention, step S4 includes:
[0021] The ceramic powder is first ground into powder, and then put into a ball mill for secondary ball milling. The secondary ball milling parameters include: a rotation speed of 200 to 300 r / min and a time of 3 to 6 hours to obtain the secondary ball milled powder.
[0022] In one embodiment of the present invention, step S5 includes:
[0023] The secondary ball-milled powder is dried, and anhydrous ethanol is added to the dried powder for wetting; after wetting, it is first pressed into a ceramic block, and then the ceramic block is pressed tightly; then the anhydrous ethanol is removed, and sintering is performed to obtain the ceramic material.
[0024] In one embodiment of the present invention, the weight percentage of anhydrous ethanol added to the dried powder is 5-8%;
[0025] The pressure for pressing the ceramic block is 100-200 MPa; the pressure for compacting the ceramic block is 200-300 MPa;
[0026] The temperature of removing the anhydrous ethanol is 90 to 150° C. and the time is 1 to 2 hours;
[0027] The sintering temperature is 600-740° C. and the sintering time is 6-8 hours.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The high entropy microwave dielectric ceramic material Na of the present invention 0.5 (LaPrNdX) 0.5 / N MoO4 has at least five elements, La, Pr, Nd, and X, at one element position, realizing high entropy component design. The dielectric properties of the material can be designed by component selection, and the sintering temperature of the material can be effectively reduced without adding sintering aids. The ceramic material has a reasonable dielectric constant, a high quality factor, and a near-zero resonant frequency temperature coefficient at a low sintering temperature, showing excellent microwave dielectric properties. At the same time, the ceramic material has good stability when placed in the air, and has the characteristics of simple chemical composition, environmental protection, non-toxicity, and pollution-free. In addition, the ceramic material is also chemically compatible with the metal electrodes Ag or Al of commonly used low-temperature co-fired ceramics, proving the feasibility of improving the microwave dielectric properties of materials through high entropy component design.
[0030] 2. The preparation method of the present invention adopts an improved solid-phase reaction method, and uses anhydrous ethanol instead of polyvinyl alcohol in the traditional solid-phase reaction method. Anhydrous ethanol is added to the dried powder and then pressed into a ceramic block. Anhydrous ethanol is easier to be removed from the pressed ceramic, which not only reduces the influence of the adhesive polyvinyl alcohol on the density and loss of the ceramic, improves the performance of the material, but also simplifies the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic flow chart of a method for preparing an environmentally friendly scheelite high-entropy microwave dielectric ceramic material provided by an embodiment of the present invention;
[0032] Figure 2a-2d The sintering temperature provided in the embodiment of the present invention has an effect on Na 0.5 (BiLaPrNdSm) 0.1 Schematic diagram of the influence of density and microwave dielectric properties of MoO4 high entropy ceramics;
[0033] Figure 3 The Na provided in the embodiment of the present invention 0.5 (BiLaPrNdSm) 0.1 XRD pattern of MoO4 ceramics and common metal electrode materials co-fired at 640℃ for 30min;
[0034] Figure 4 The XRD patterns of high entropy ceramics at the optimal sintering temperature in Examples 1, 2 and 3 provided in the embodiments of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.
[0036] This embodiment provides an environmentally friendly scheelite high entropy microwave dielectric ceramic material, which has a structural expression of Na 0.5 (LaPrNdX) 0.5 / N MoO4, wherein X is selected from at least two of Bi, Ce, Sm, Eu, and Y, and N is the sum of the number of element species of La, Pr, Nd, and X.
[0037] Specifically, the ceramic material Na 0.5 (LaPrNdX) 0.5 / N In MoO4, X is selected from at least two of Bi, Ce, Sm, Eu, and Y, that is, X can be two, three, four, or five of Bi, Ce, Sm, Eu, and Y, and N can be 5, 6, 7, or 8, so that the ceramic material has 5 elements, 6 elements, 7 elements, or 8 elements at one element position at the same time.
[0038] It can be understood that when X is selected from two of Bi, Ce, Sm, Eu, and Y, the sum of the number of element types of La, Pr, Nd, and X is 5. For example, Na 0.5 (BiLaPrNdSm) 0.1 MoO4; when X is selected from three of Bi, Ce, Sm, Eu, and Y, the sum of the number of element types of La, Pr, Nd, and X is 6, for example, Na 0.5 (BiLaPrNdSmEu) 0.5 / 6 MoO4; when X is selected from four of Bi, Ce, Sm, Eu, and Y, the sum of the number of element types of La, Pr, Nd, and X is 7, for example, Na 0.5 (BiLaPrNdSmEuY) 0.5 / 7 MoO4; when X is selected from five of Bi, Ce, Sm, Eu, and Y, the sum of the number of element types of La, Pr, Nd, and X is 8, for example, Na 0.5 (BiCeLaPrNdSmEuY) 0.5 / 8 MoO4.
[0039] The ceramic material Na 0.5 (LaPrNdX) 0.5 / N In MoO4, at least five elements, including La, Pr, Nd, and X, exist at the same element position, which has a high degree of disorder and forms a high entropy configuration.
[0040] It should be noted that the ceramic material Na 0.5 (LaPrNdX) 0.5 / N The types of MoO4 are not limited to the above examples. Materials that meet the above principles belong to Na 0.5 (LaPrNdX) 0.5 / N Coverage of MoO4.
[0041] Specifically, the ceramic material Na 0.5 (LaPrNdX) 0.5 / N The sintering temperature of MoO4 is 600~740℃, and it can be sintered in a lower sintering range. 0.5 (LaPrNdX) 0.5 / N The sintering temperature at which the MoO4 ceramic system achieves optimal performance.
[0042] Specifically, the ceramic material Na 0.5 (LaPrNdX) 0.5 / N Relative dielectric constant ε of MoO4 r It is 10~16, the quality factor Qf is 20000~50000GHz, and the temperature coefficient of resonant frequency TCF is -30~-60ppm / ℃.
[0043] Specifically, the ceramic material Na 0.5 (LaPrNdX) 0.5 / N MoO4 is environmentally friendly and non-toxic and can be co-fired with Ag electrodes or Al electrodes.
[0044] Exemplarily, the environmentally friendly scheelite high entropy microwave dielectric ceramic material is a high entropy ceramic Na 0.5 (BiLaPrNdSm) 0.1 MoO4, the ceramic material is the first successfully prepared high entropy ultra-low temperature co-fired ceramic (ULTCC) microwave dielectric ceramic material, which can be sintered densely at an ultra-low sintering temperature of 600°C and maintain a very high density within 640-880°C, with a density greater than 97%; and Na 0.5 (BiLaPrNdSm) 0.1 MoO4 ceramic material also has excellent microwave dielectric properties: dielectric constant ε r =15.7, quality factor Qf = 33000GHz (@8.5GHz), resonant frequency temperature coefficient TCF = -37.8ppm / ℃; In addition, Na 0.5 (BiLaPrNdSm) 0.1 MoO4 ceramic materials are also chemically compatible with the metal electrodes Ag or Al of commonly used low temperature co-fired ceramics (LTCC).
[0045] The high entropy microwave dielectric ceramic material Na 0.5 (LaPrNdX) 0.5 / N MoO4 has at least five elements, La, Pr, Nd, and X, at one element position, realizing high entropy component design. The dielectric properties of the material can be designed by component selection, and the sintering temperature of the material can be effectively reduced without adding sintering aids. The sintering temperature is 600-740°C, which can be lower than 700°C. The ceramic material has a reasonable dielectric constant, a high quality factor, and a near-zero resonant frequency temperature coefficient at a low sintering temperature, showing excellent microwave dielectric properties. At the same time, the ceramic material has good stability when placed in the air, and has the characteristics of simple chemical composition, environmental protection, non-toxicity, and pollution-free. In addition, the ceramic material is also chemically compatible with the metal electrodes Ag or Al of commonly used low-temperature co-fired ceramics, proving the feasibility of improving the microwave dielectric properties of the material through high entropy component design, thereby meeting the technical requirements of LTCC substrate materials.
[0046] This embodiment also provides a method for preparing a molybdenum-based microwave dielectric ceramic material, which is used to prepare the molybdenum-based microwave dielectric ceramic material described in the above embodiment.
[0047] See also Figure 1 , Figure 1A schematic flow chart of a method for preparing an environmentally friendly scheelite high entropy microwave dielectric ceramic material provided in an embodiment of the present invention. The preparation method comprises the following steps:
[0048] S1, according to the structural expression of ceramic materials is Na 0.5 (LaPrNdX) 0.5 / N MoO4 weighs Na2CO3, La2O3, Pr2O3, Nd2O3, MoO3 and rare earth oxides as raw materials, wherein X is selected from at least two of Bi, Ce, Sm, Eu, and Y, N is the sum of the element types of La, Pr, Nd, and X, and the rare earth oxides are selected from at least two of Bi2O3, CeO2, Sm2O3, Eu2O3, and Y2O3.
[0049] Specifically, the rare earth oxides are oxides corresponding to the rare earth elements Bi, Ce, Sm, Eu, and Y, namely Bi2O3, CeO2, Sm2O3, Eu2O3, and Y2O3. The molar ratio of the rare earth elements Bi, Ce, Sm, Eu, and Y is 1:1:1:1:1, and the molar ratio of the corresponding rare earth oxides Bi2O3, CeO2, Sm2O3, Eu2O3, and Y2O3 is 1:2:1:1:1. For example, if X selects Ce and Sm, the rare earth oxides are CeO2 and Sm2O3, and the molar ratio of CeO2 and Sm2O3 is 2:1; if X selects Bi, Eu, and Sm, the rare earth oxides are Bi2O3, Eu2O3, and Sm2O3, and the molar ratio of Bi2O3, Eu2O3, and Sm2O3 is 1:1:1.
[0050] Specifically, Na2CO3, La2O3, Pr2O3, Nd2O3, Bi2O3, CeO2, Sm2O3, Eu2O3, Y2O3, and MoO3 all have analytical purity. For example, the purity of Na2CO3 is 99%, the purity of MoO3 is 99.95%, the purity of La2O3, Pr2O3, Nd2O3, Sm2O3, and Eu2O3 are all 99.5%, the purity of Y2O3 is 99%, the purity of Bi2O3 is 99.9%, and the purity of CeO2 is 99%.
[0051] Furthermore, the rare earth oxides La2O3, Pr2O3, Nd2O3, Bi2O3, CeO2, Sm2O3, Eu2O3, and Y2O3 are placed in a muffle furnace for pretreatment before use. The pretreatment conditions are to keep warm at 700-850°C for 3-6 hours. For example, the rare earth oxides are placed in a muffle furnace and kept warm at 780°C for 4 hours.
[0052] S2. The raw materials are mixed evenly through a primary ball milling process to obtain a primary ball milled powder.
[0053] Specifically, the raw materials, zirconium balls and anhydrous ethanol (ball milling medium) are added into a ball milling jar at a mass ratio of 1:2:1, and after being sealed, the jar is placed on a planetary ball mill for a first ball milling to mix evenly. The first ball milling parameters include: a rotation speed of 200 to 300 r / min, a time of 3 to 6 hours, and a first ball milling powder is obtained.
[0054] S3, pre-sintering the primary ball-milled powder to obtain pre-sintered ceramic powder.
[0055] Specifically, the primary ball-milled powder is first dried. For example, the primary ball-milled powder is placed in a common oven and dried at 100° C. for 24 hours; the dried powder is then pre-sintered at 550° C. to 650° C. for 4 to 8 hours to form a material phase, thereby obtaining a pre-fired ceramic powder.
[0056] S4, performing secondary ball milling on the ceramic powder to obtain secondary ball milled powder.
[0057] Specifically, the ceramic powder can be ground manually, and then put into a ball mill for secondary ball milling to further refine the particle size of the powder. The secondary ball milling parameters include: a rotation speed of 200 to 300 r / min, a time of 3 to 6 hours, and a secondary ball milled powder is obtained.
[0058] S5, pressing and sintering the secondary ball-milled powder to obtain the ceramic material.
[0059] Specifically, the secondary ball-milled powder is dried, and anhydrous ethanol is added to the dried powder for wetting; after wetting, it is first pressed into a ceramic block, and then the ceramic block is pressed tightly; then the anhydrous ethanol is removed, and sintering is performed to obtain the ceramic material.
[0060] In an optional embodiment, the secondary ball-milled powder is dried at 100°C for 24 hours; 5-8% by weight of anhydrous ethanol is added to the dried powder for wetting; after wetting, it is first pressed into a ceramic block at a pressure of 100-200 MPa using a manual press, and then maintained at a pressure of 200-300 MPa for 3 minutes in an isostatic press to compact it; then, it is kept warm at 90-150°C for 1-2 hours to remove the anhydrous ethanol, and finally, it is kept warm at 600-740°C for 6-8 hours for sintering to obtain an environmentally friendly low-temperature sintered molybdenum-based high-entropy microwave dielectric ceramic material.
[0061] Exemplarily, the ceramic block is in the shape of a cylinder with a diameter of 10 mm and a height of 5 mm.
[0062] At present, most microwave dielectric ceramic materials are prepared by the traditional solid phase reaction method, which uses polyvinyl alcohol (PVA) as a binder and then removes it by keeping it at 550°C for 4 hours. However, as the sintering temperature of the ceramic continues to decrease (<550°C), the PVA introduced in the granulation process cannot be completely eliminated, and the residual PVA reduces the density of the ceramic and increases the loss of the ceramic. The preparation method of this embodiment adopts an improved solid phase reaction method, using anhydrous ethanol to replace the polyvinyl alcohol in the traditional solid phase reaction method, adding anhydrous ethanol to the dried powder and then pressing it into a ceramic block. Anhydrous ethanol is easier to be removed from the pressed ceramic, which not only reduces the influence of the binder polyvinyl alcohol on the density and loss of the ceramic, but also improves the performance of the material, and simplifies the preparation process, and the preparation process is simple.
[0063] This embodiment further illustrates the molybdenum-based microwave dielectric ceramic material and the preparation method thereof through the following examples.
[0064] Example 1
[0065] Prepare the raw materials Na2CO3, Pr2O3, CeO2, Y2O3, La2O3, Nd2O3 and MoO3 of analytical purity in a molar ratio of 5:1:2:1:1:1:20, and put the weighed Pr2O3, CeO2, Y2O3, La2O3 and Nd2O3 into a muffle furnace and keep it at 780℃ for 4h. Then, the prepared raw materials, zirconium balls and anhydrous ethanol are ball-milled once in a mass ratio of 1:2:1 to fully mix, and the ball milling speed is 200-300r / min for 4h to obtain a ball-milled powder. Put the ball-milled powder into a common oven and dry it at 100℃ for 24h, then put the dried powder into a crucible and pre-fire at 550℃ for 4 hours to obtain a pre-fired ceramic powder. After the pre-fired ceramic is manually ground, it is placed in a ball mill again for secondary ball milling at a speed of 200-300 r / min for 4 hours to obtain secondary ball milled powder. The secondary ball milled powder is dried at 100°C for 24 hours, and then 5% by weight of anhydrous ethanol is added to the dried powder to moisten it. After wetting, it is first pressed into a cylindrical ceramic block with a diameter of 10 mm and a height of 5 mm at a pressure of 100 MPa using a manual press, and then pressed tightly at a pressure of 200 MPa in an isostatic press. The compacted ceramic is first kept at 120°C for 1 hour to remove the anhydrous ethanol, and then sintered in air at 600-680°C at several temperature points of 600°C, 620°C, 640°C, 660°C, and 680°C for 6 hours to obtain an environmentally friendly low-temperature sintered high-entropy microwave dielectric ceramic material Na 0.5 (PrCeYLaNd) 0.1 MoO4.
[0066] Furthermore, a network analyzer (4990A Agilent) and a temperature chamber (DELTA 9023, Delta Design) were used to analyze the TE 01δ Mode Test Na 0.5 (PrCeYLaNd) 0.1 Microwave dielectric properties of MoO4 ceramic samples, where the calculation formula of the resonant frequency temperature coefficient TCF is as follows:
[0067]
[0068] In the formula, f 25 is the resonant frequency of the sample at 25°C, in GHz, f 85 is the resonant frequency of the sample at 85°C, in GHz.
[0069] After testing, Na 0.5 (PrCeYLaNd) 0.1 MoO4 ceramics are sintered densely in air at 660℃, and the microwave dielectric properties are optimal. The dielectric constant under microwave is ε r It is 12.3 (@9.9GHz), the quality factor Q is 1850, the Qf is 21000GHz, and the resonant frequency temperature coefficient TCF under microwave is -44ppm / ℃ (25~85℃).
[0070] Example 2
[0071] Prepare the raw materials Na2CO3, Bi2O3, Pr2O3, La2O3, Nd2O3, Sm2O3 and MoO3 of analytical purity in a molar ratio of 5:1:1:1:1:1:20, and put the weighed Bi2O3, Pr2O3, La2O3, Nd2O3 and Sm2O3 into a muffle furnace and keep it at 780℃ for 4h. Then, the prepared raw materials, zirconium balls and anhydrous ethanol are ball-milled once in a mass ratio of 1:2:1 to fully mix, and the ball milling speed is 200-300r / min for 4h to obtain a ball-milled powder. Put the ball-milled powder into a common oven and dry it at 100℃ for 24h, then put the dried powder into a crucible and pre-fire at 650℃ for 4 hours to obtain a pre-fired ceramic powder. After the pre-fired ceramic is manually ground, it is placed in a ball mill again for secondary ball milling at a speed of 200-300r / min for 4 hours to obtain secondary ball milled powder. The secondary ball milled powder is dried at 100°C for 24 hours, and then 5% by weight of anhydrous ethanol is added to the dried powder to moisten it. After wetting, it is first pressed into a cylindrical ceramic block with a diameter of 10mm and a height of 5mm under a pressure of 100MPa using a manual press, and then pressed tightly at a pressure of 300MPa in an isostatic press. The compacted ceramic is first kept at 120°C for 2 hours to remove the anhydrous ethanol, and then sintered in air at 560-1000°C at 560°C, 600°C, 640°C, 680°C, 720°C, 800°C, 880°C, and 1000°C for 6 hours to obtain an environmentally friendly low-temperature sintered high-entropy microwave dielectric ceramic material Na 0.5 (BiLaPrNdSm) 0.1 MoO4.
[0072] Furthermore, the Na 0.5 (BiLaPrNdSm) 0.1 Density, relative density and dielectric properties of MoO4 ceramics. A network analyzer (4990A Agilent) and a temperature chamber (DELTA 9023, Delta Design) were used to analyze the MoO4 ceramics using the closed cavity resonance method. 01δ Mode Test Na 0.5 (BiLaPrNdSm) 0.1 Microwave dielectric properties of MoO4 ceramic samples.
[0073] See also Figure 2a-2d , Figure 2a-2d The sintering temperature provided in the embodiment of the present invention has an effect on Na 0.5 (BiLaPrNdSm) 0.1 Schematic diagram of the influence of density and microwave dielectric properties of MoO4 high entropy ceramics. Figure 2aRepresents density and relative density maps, Figure 2b Represents the dielectric constant ε r Atlas, Figure 2c Represents the quality factor Qf spectrum, Figure 2d Represents the resonant frequency temperature coefficient TCF spectrum. Figure 2a-2d It can be seen that the relative density, dielectric constant and Qf value first increase and then decrease with the increase of sintering temperature, while the fluctuation of TCF value in the entire sintering temperature range of 560℃ to 1000℃ is less than 5ppm / ℃. 0.5 (BiLaPrNdSm) 0.1 MoO4 ceramics are densely sintered at an ultra-low sintering temperature of 600°C and maintain a high density within the sintering temperature range of 640-880°C, with a density greater than 97%. 0.5 (BiLaPrNdSm) 0.1 MoO4 ceramics have the best microwave dielectric properties: dielectric constant ε r It is 16 (@8.5GHz), the quality factor Q is 3900, the Qf is 33000GHz, and the resonant frequency temperature coefficient TCF under microwave is -38pm / ℃ (25~85℃).
[0074] Furthermore, the Na 0.5 (BiLaPrNdSm) 0.1 MoO4 and metal powder were co-fired for 30 minutes, and the XRD after co-firing was tested. Figure 3 , Figure 3 The Na provided in the embodiment of the present invention 0.5 (BiLaPrNdSm) 0.1 XRD pattern of MoO4 ceramics and common metal electrode materials co-fired at 640℃ for 30min. Figure 3 It can be seen that only Na 0.5 (BiLaPrNdSm) 0.1 The diffraction peaks of MoO4 and metals mean that the ceramics do not chemically react with either Ag or Al at the sintering temperature.
[0075] Example 3
[0076] Prepare the raw materials Na2CO3, Bi2O3, Pr2O3, La2O3, Nd2O3, CeO2 and MoO3 of analytical purity in a molar ratio of 5:1:1:1:1:2:20, and put the weighed Bi2O3, Pr2O3, La2O3, Nd2O3 and CeO2 into a muffle furnace and keep it at 780℃ for 4h. Then, the prepared raw materials, zirconium balls and anhydrous ethanol are ball-milled once in a mass ratio of 1:2:1 to fully mix, and the ball milling speed is 200-300r / min for 4h to obtain a ball-milled powder. Put the ball-milled powder into a common oven and dry it at 100℃ for 24h, then put the dried powder into a crucible and pre-fire at 650℃ for 4 hours to obtain a pre-fired ceramic powder. After the pre-fired ceramic is manually ground, it is placed in a ball mill again for secondary ball milling at a speed of 200-300r / min for 4 hours to obtain secondary ball milled powder. The secondary ball milled powder is dried at 100°C for 24 hours, and then 5% by weight of anhydrous ethanol is added to the dried powder to moisten it. After wetting, it is first pressed into a cylindrical ceramic block with a diameter of 10mm and a height of 5mm by a manual press at a pressure of 100MPa, and then pressed tightly in an isostatic press at a pressure of 200MPa. The compacted ceramic is first kept at 120°C for 2 hours to remove the anhydrous ethanol, and then sintered at 640-740°C at 640°C, 660°C, 680°C, 700°C, 720°C, and 740°C for 6 hours to obtain an environmentally friendly low-temperature sintered high-entropy microwave dielectric ceramic material Na 0.5 (BiLaPrNdCe) 0.1 MoO4.
[0077] Furthermore, a network analyzer (4990A Agilent) and a temperature chamber (DELTA 9023, Delta Design) were used to analyze the TE 01δ Mode Test Na 0.5 (BiLaPrNdCe) 0.1 Microwave dielectric properties of MoO4 ceramic samples.
[0078] After testing, Na 0.5 (BiLaPrNdCe) 0.1 MoO4 ceramics are sintered densely in air at 720℃, and the microwave dielectric properties are optimal. The dielectric constant under microwave is ε r The quality factor Q is 2500, the Qf is 22000GHz, and the temperature coefficient of resonant frequency TCF under microwave is -32ppm / ℃ (25~85℃).
[0079] See also Figure 4 , Figure 4The XRD patterns of high entropy ceramics at the optimal sintering temperature in Example 1, Example 2, and Example 3 provided in the present invention. Figure 4 It can be seen that Na 0.5 (PrCeYLaNd) 0.1 MoO4、Na 0.5 (BiLaPrNdSm) 0.1 MoO4 and Na 0.5 (BiLaPrNdCe) 0.1 All three MoO4 crystals have ABO4 scheelite tetragonal structure, belonging to the space group I41 / a (No.88), Na + The trivalent cations are statistically averaged and randomly distributed at the A position of the ABO4 structure.
[0080] The Na 0.5 (LaPrNdX) 0.5 / N The MoO4 high-entropy ceramic system is the first successfully prepared high-entropy ULTCC microwave dielectric ceramic material. It can achieve a lower sintering temperature and excellent microwave dielectric properties without adding sintering aids. It is chemically compatible with commonly used LTCC metal electrodes Ag or A1, and the microwave dielectric properties of the material can be improved through high-entropy component design.
[0081] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. An environmentally friendly scheelite high entropy microwave dielectric ceramic material, characterized in that: The structural expression of the ceramic material is Na 0.5 (LaPrNdX) 0.5 / N MoO4, wherein X is selected from at least two of Bi, Ce, Sm, Eu, and Y, and N is the sum of the number of element species of La, Pr, Nd, and X.
2. The environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 1 is characterized in that: The sintering temperature of the ceramic material is 600-740°C.
3. The environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 1 is characterized in that: The relative dielectric constant of the ceramic material is 10-16, the quality factor is 20000-50000 GHz, and the resonant frequency temperature coefficient is -30--60 ppm / °C.
4. A method for preparing an environmentally friendly scheelite high entropy microwave dielectric ceramic material, characterized in that: Includes steps: S1, according to the structural expression of ceramic materials Na 0.5 (LaPrNdX) 0.5 / N MoO4 weighs Na2CO3, La2O3, Pr2O3, Nd2O3, MoO3 and rare earth oxides as raw materials, wherein X is selected from at least two of Bi, Ce, Sm, Eu, and Y, N is the sum of the element types of La, Pr, Nd, and X, and the rare earth oxides are selected from at least two of Bi2O3, CeO2, Sm2O3, Eu2O3, and Y2O3; S2, mixing the raw materials uniformly through a primary ball milling process to obtain a primary ball milled powder; S3, pre-sintering the primary ball-milled powder to obtain a pre-sintered ceramic powder; S4, performing secondary ball milling on the ceramic powder to obtain secondary ball milled powder; S5, pressing and sintering the secondary ball-milled powder to obtain the ceramic material.
5. The method for preparing the environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 4, characterized in that: Step S1 includes: La2O3, Pr2O3, Nd2O3 and rare earth oxides are placed in a muffle furnace for pretreatment. The pretreatment conditions are 700-850°C and kept warm for 3-6 hours.
6. The method for preparing the environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 4, characterized in that: Step S2 includes: The raw materials, zirconium balls and anhydrous ethanol are placed in a ball mill according to a mass ratio of 1:2:1 for primary ball milling. The primary ball milling parameters are: speed 200-300 r / min, time 3-6 h, to obtain the primary ball milled powder.
7. The method for preparing the environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 4, characterized in that: Step S3 includes: The once ball-milled powder is dried, and the dried powder is pre-sintered at 550-650° C. for 4-8 hours to obtain the pre-sintered ceramic powder.
8. The method for preparing the environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 4, characterized in that: Step S4 includes: The ceramic powder is first ground into powder, and then put into a ball mill for secondary ball milling. The secondary ball milling parameters include: a rotation speed of 200 to 300 r / min and a time of 3 to 6 hours to obtain the secondary ball milled powder.
9. The method for preparing the environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 4, characterized in that: Step S5 includes: The secondary ball-milled powder is dried, and anhydrous ethanol is added to the dried powder for wetting; after wetting, it is first pressed into a ceramic block, and then the ceramic block is pressed tightly; then the anhydrous ethanol is removed, and sintering is performed to obtain the ceramic material.
10. The method for preparing the environmentally friendly scheelite high entropy microwave dielectric ceramic material according to claim 9, characterized in that: Adding anhydrous ethanol in a weight percentage of 5 to 8% to the dried powder; The pressure for pressing the ceramic block is 100-200 MPa; the pressure for compacting the ceramic block is 200-300 MPa; The anhydrous ethanol is removed at a temperature of 90 to 150° C. for 1 to 2 hours; The sintering temperature is 600-740° C. and the sintering time is 6-8 hours.
Citation Information
Patent Citations
Ultra-low temperature sintering microwave dielectric ceramic material system, and preparation method and application thereof
CN108911746A
Ultra-low temperature sintered sodium-based composite microwave dielectric ceramic material and preparation method thereof
CN110668817A
Molybdic acid rare earth-based medium / high-entropy ceramic material as well as preparation method and application thereof
CN115286383A
Method for controlling characteristics of microwave dielectric porcelain composition and composition obtained thereby
JP2006335599A
Microwave dielectric ceramic composition
US20030100437A1